Benefit sharing in genomic and biobanking research in Uganda: Perceptions of researchers and research ethics committee members - Mwaka, Erisa Sabakaki; Bagenda, Godfrey; Sebatta, Deborah Ekusai; Nabukenya, Sylvia; Munabi, Ian (Frontiers in Genetics, 2022)
Background: Genomic and biobanking research has increased in Africa over the past few years. This has raised pertinent ethical, legal, and societal concerns for stakeholders such as sample or data ownership, commercialization, and benefit sharing. There is limited awareness of the concept of benefit sharing by stakeholders in sub-Saharan Africa. Objective: This study aimed to explore the perceptions of researchers and research ethics committee members on benefit sharing in international collaborative genomic and biobanking research. Methods: Qualitative in-depth interviews were conducted with 15 researchers and 19 research ethics committee members. A thematic approach was used to interpret the results. Results: Six themes emerged from the data and these included perceptions on the benefits of genomic and biobanking research; discussion of benefit sharing with participants during the informed consent process; legal implications of benefit sharing and the role of material transfer agreements; equity and fairness in sharing the benefits of genomic research; perceived barriers to fair benefit sharing; and recommendations for fostering fair and equitable benefit sharing in genomic and biobanking research. Most respondents clearly understood the various forms of benefits of genomic and biobanking research and opined that such benefits should be fairly and equitably shared with low and middle-income country researchers and their institutions, and research communities. The perceived barriers to the fair benefit sharing unfavorable include power disparities, weak research regulatory frameworks, and lack of scientific integrity. Conclusion: Overall, respondents believed that the distribution of the advantages of genomic and biobanking research in North-South collaborative research was not equitable nor fair, and that the playing field was not leveled. Therefore, we advocate the following for fair and equitable benefit sharing: Building the capacities and empowering research scientists in developing nations; strengthening regulatory frameworks and extending the purview of the research ethics committee in the development and implementation of material transfer agreements; and meaningfully involving local research communities in benefit sharing negotiations.